The Agreement Level of Tuberculin Skin Test (TST) and T-SPOT.TB Examinations in Detecting Latent Tuberculosis Infection in Illicit Drug Users - Maulana Eka Hamdani, S; ., Reviono; Gusti Bagus Indro Nugroho, I (KnE Life Sciences, 2019)
World Health Organization (WHO) reported that a third of the world’s populations develop latent tuberculosis infection (LTBI). Illicit drug users are at risk of suffering LTBI which potentially developing into active tuberculosis (TB). There is no gold standard diagnostic for LTBI and it is presumed that immune responses play an important role in LTBI. This study aimed o evaluate the ideal diagnostic tool to fill the absence of a gold standard and the effect of illicit drugs on the immune system. This was a cross sectional study conducted in illicit drug clinic, Methadone Maintenance Therapy (MMT) program of Dr. Moewardi Hospital, and MMT program of Puskesmas Manahan Surakarta, from February to March 2018. Total subjects were 24 respondents consisting of 5 respondents with TST (+) and 4 with T-SPOT.TB (+). We measured the agreement level of TST and T-SPOT.TB was moderate (k= 0.591, p= 0.003), the relationship of absolute cluster of differentiation 4 (CD4) to TST induration (r= 0.077, p= 0.719), the relationship between absolute CD4 and T-SPOT.TB spot-forming units (SFUs) ESAT-6 (r= -0.238, p= 0.262); CFP-10 (r= -0.117, p= 0.585); and the highest ESAT-6/CFP-10 (r= -0.033, p= 0.879). Tuberculin skin test and T-SPOT.TB have their own strengths and weaknesses, but in this study TST is slightly superior to T-SPOT.TB with moderate agreement level. Keywords: LTBI, TST, T-SPOT.TB, illicit drug